Conflict as a possible catalyst for democratic relations in the work of the Family Health team - Iramildes Souza Silva; Cássia Irene Spinelli Arantes; Cinira Magali Fortuna (SciELO, 2019)
ABSTRACT Objective: To analyze conflict situations in the basic care team as possible catalysts of democratic relations at work, favoring team performance. Method: A qualitative study with a family health team from a municipality in the interior of São Paulo State. The data collected included systematic observation and interviews with workers who were organized and analyzed from the confrontation with the theoretical reference of the health work process. Thematic content analysis was used. Results: 16 workers participated. The data are organized into two thematic categories: the reception of unity as a place where conflicts become more explicit, and the conflict as an opening for building democratic relationships in teamwork. Conclusion: Receiving users at the reception and who will or will not work in this space reveals different values and conceptions about the care each professional provides, and constitutes a situation that generates conflict. However, opposing ideas in the conflict are fruitful because they are able to complement each other and provide a qualitative leap in team relations, with a tendency to influence a reduction in the vulnerabilities of the relations between the subjects. This is a pressing and current need in the discussion involving the reorganization of health practices.